Tracing London's urban living room - Anak Agung Ayu Suci Warakanyaka (Department of Architecture Faculty of Engineering Universitas Indonesia, 2021)
Responding to the rapid development of indoor public interiors motored by commercial activities, this paper argues that an alternative form that is more inclusive is needed to foster healthier and more socially equitable interactions in the city. It frames urban living room, a micro-scale outdoor interior development that aims to inject domestic experiences into the existing urban environment, as the antithesis of the exclusive indoor public interiors. Utilising tracing as a mode of inquiry to look at two case studies of the urban living room in London, UK, this paper aims to reveal the spatial mechanism that makes this public interior provide the much needed intimate experiences that make the city habitable. The finding of this study suggests that the interior mechanisms used by urban living room provide scalar confrontation and heighten sensual experience that fosters intimate social interactions and inclusivity for all urban dwellers.